Blockmodeling of Valued Networks - Nordlund, Carl; Žiberna, Aleš (Advances in Network Clustering and Blockmodeling, 2020)
This chapter provides an overview of approaches, classical as well as recent innovations, to the clustering/blockmodeling of valued networks. It focuses exclusively on one‐mode, single‐relational, non‐signed, possibly directional and possibly with self‐ties, valued networks and the particularities that apply to the clustering/blockmodeling of such networks. The chapter describes the different types of valued network data that exist. This is followed by a description of various transformations that can be applied to such data prior to clustering methods being used. An overview of clustering methods and heuristics for valued networks follows, divided into indirect and direct approaches. The chapter also demonstrates various clustering/blockmodeling techniques on two example valued networks. As is evident in these examples, two or more approaches can be equally “good”, all depending on whether their respective clustering methods and pre‐ and post‐cluster transformations capture what we intend to capture in our analysis.